(3cJGH ajg UdhGJ Ydi GdfHj Udi Gddg Ydjg hSdes - (3GdHjLGhj, eMeO Hf eMeO GdYQHjs ((3eMeO Hf eMeO GdYQHj GdHjLGhj GdJQGHjs)
(3ChdgG (B:s
(3fGbU GdChd, hChdg(B: (3Gddg YR hLd (B{(3Ef Gddg hedGFcJg jUdhf Ydi GdfHj jG CjgG GdPjf BefhG UdhG Ydjg hSdehG JSdjeG(B}s
(3BNQgG (B:s
(3hUdi Gddg Ydi SjOfG eMeO NGJe GdfHjjf hEeGe GdeQSdjf hYdi Bdg hUMHg hSde JSdjeG cKjQGs
(3HNW GdeDda, Hg QShe dbHQ GdQShd hCHh HcQ hYeQ Hf GdNWGH hQShe CNQi OGNd EWGQGJ, haj BNQg bUjOI eOM GdQShd JSei NjQ GdHQjI aj eOjM bUO GdgGejIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdJUha hGdBOGH GdTQYjIs